Activation energy, temperature coefficient and Q10 value estimations of the growth of 2,4-dinitrophenol-degrading Bacterium on 2,4-dinitrophenol - Muhammad Yakasai, Hafeez; Md. Zin, Noor Suffiah; Shukor, Mohd Yunus (Hibiscus Publisher, 2022)
In addition to its use as a pesticide, the chemical compound known as 2,4-dinitrophenol (2,4-DNP) is also utilized in the creation of wood preservatives and colors. Symptoms of acute (short-term) exposure to 2,4-DNP in humans include nausea or vomiting, sweating, headaches, disorientation, and a loss of weight. This type of exposure occurs when the substance is consumed orally. There are a few different models that may be used to simulate the growth rate of microorganisms on a variety of different medium at a range of temperatures. These models can be found online. One of the models that is employed the most frequently is the Arrhenius model, in part because it has a limited number of parameters. The development and metabolic activities of bacteria on the substrates they are grown on are commonly influenced by temperature. Temperature can also affect the growth of germs. Microbes are extremely sensitive to changes in temperature because of their small size. A discontinuous apparent activation energy with a chevron-like graph was used in order to describe the growth of a 2,4-dinitrophenol-degrading bacterium on 2,4-dinitrophenol. The break point of the graph was set at 28.05 °C. This was done so that the development of the bacterium could be described. Following the conclusion of the regression analysis, two temperature ranges for activation were determined. These temperature ranges were 20-27 °C and 30-42 °C, and their associated activation energies were 41.72 and 84.72 kilojoules per mole, respectively. It was anticipated that the Q10 value would be 2.905 and that the theta value would be 1.11 when considering the temperature range that was considered (30-42 °C). Due to the all-encompassing scope of this study, it is particularly useful for forecasting the effect of temperature on the breakdown and fate of 2,4-dinitrophenol during bioremediation.